MORAL EDUCATION FOR FORGIVENESS IN CHILDREN - ABREU, Eloá Losano de (2018)
This article presents the results of an intervention for forgiveness performed with 17 children with a mean age of 7 years and 6 months (SD = 0.70). The method used was quasi-experimental, with participants responding to an Inter-view of Forgiveness at the beginning and at the end of the intervention. After the initial interview, participants were randomly divided into experimental and control groups. The children of the experimental group participated in the ac-tivities for forgiveness outlined for the intervention. The children of the control group were kept in the normal classes of the institution. The results indicated that forgiveness was associated with apology and reconciliation. The compari-son between the pre-test and the post-test showed that children in the experi-mental group had a significant increase in the degree of forgiveness, a signifi-cant decrease in the degree of anger, and an increase in the frequency of for-giveness as a choice for the resolution of interpersonal conflicts. In conclusion, for children in this age group, apology and reconciliation function as represen-tations of forgiveness.